Implementasi Sistem Informasi Keuangan, Kompetensi Pegawai dan Evaluasi Manajemen Terhadap Efektifitas Pengelolaan Keuangan - Irwandi, Irwandi (Jurnal Manajemen, 2019)
Financial management is one of the factors that determine the achievement of organizational goals. In order for financial management (budget) to run in an orderly and accountable financial information system. To further optimize the work of information systems so that effectiveness can be achieved requires implementation activities, employee competencies and management evaluation of the financial information system. This study aims to analyze: 1). Analyzing the influence of the implementation of financial information systems on the effectiveness of financial management, 2). Analyzing the influence of employee competency on financial management effectiveness 3). Analyze the influence of management evaluations on the effectiveness of financial management in the Open University Distance Learning Program Unit throughout Indonesia.The study was conducted using quantitative descriptive method, the research sampling used purposive sampling non probability with a total sample of 117 respondents. The data analysis technique used is regression analysis using Partial Least Square (PLS). The results showed that the implementation of financial information systems had a significant effect on the effectiveness of financial management, employee competence had a significant effect on the effectiveness of financial management and management evaluation also had a significant effect on the effectiveness of financial management. Determination coefficient value obtained is 64.80%, it can be concluded that the implementation of financial information systems, employee competencies and management evaluation of effective financial management.